The development of chemistry practicum e-module based on simple-practice - Nelius Harefa; Leony Sanga Lamsari Purba (Jurnal Pendidikan Kimia (JPKim), 2019)
Practicum is an important element in chemistry. In chemistry learning with practical methods students are given the opportunity to be creative, find, or prove a phenomenon that he experienced and the concepts his learned. Therefore, it is important to develop the learning method using practicum to accommodate the progress and needs of the times so that learning is close to students so that learning becomes meaningful. In this research, the development of digital integrated chemistry practicum modules based on simple practice is carried out. The research sample consisted of 248 students and 26 chemistry teachers, and was validated by 3 expert judges. In the initial stage, the module developed is validated by expert judges. The validation results show that the module is categorized as valid in terms of content eligibility, language feasibility, and presentment eligibility with an average score of 3.81 (scale 4). In the final stage, a module testing is conducted for chemistry students and teachers in the form of collecting responses. Chemistry teacher response results indicate that the module is feasible to be used as a source of student learning on chemistry practicum class XI high school even semester with an average score of 3.78 (scale 4). The results of the students' responses showed that the module was appropriate for them to use as a source of learning on chemistry practicum with an average score of 3.79 (scale 4). The results of student responses on the presentment eligibility aspect showed the highest value of 3.98 (scale 4), the module developed was presented digitally integrated which can be accessed online.Keywords: Chemistry; e-module; practicum; simple-practice